The role of epidermal growth factor and cholinergic receptor agonists and antagonists in MAPK signal transduction in K562 cells - AYDIN OMAY, BANU (My University, 2023)
Objective: Muscarinic receptors (M1-M5) are members of the G protein-coupled receptor superfamily and are effective in physiological functions through G proteins. Recent studies suggested that cholinergic receptors mediate cellular activities in hematopoietic cells. The aim of this study was to investigate the potential role of mitogen-activated protein kinases (MAPK) signaling extracellular signalregulated kinases 1 and 2 (ERK1/2)/phosphorylated ERK1/ (pERK1/2) pathways in chronic myeloid leukemia (K562) cells. Materials and Methods: Chronic myeloid leukemia cells were cultured. Cells were incubated in the presence of muscarinic receptor agonist, antagonist and epidermal growth factor (EGF). To detect MAPK activation, ERK/pERK protein expression levels were determined by western blot method techniques. Results: Our study results showed that cholinergic agents and EGFs affect the MAPK pathway in the human K562 cell line. Conclusion: Cholinergic and EGF receptors may affect the MAPK pathway in K562 cells. Conclusion: Cholinergic and EGF receptors may affect the MAPK pathway in K562 cells.
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary; G protein coupled receptor; Carbachol; Epidermal growth factor; Mitogen-activated protein kinase; Chronic myeloid leukemia